THE ROLE OF SURAU AND TAREKAT IN TRADITIONAL ISLAMIC EDUCATION IN 20th CENTURY AD. - Satria, Rengga; Lionar, Uun; Rivauzi, Ahmad (TARBAWY: Indonesian Journal of Islamic Education, 2022)
Abstract. This study aims to reveal the contribution of the surau and tarekat to traditional Islamic education in Minangkabau in the 20th century AD. This research is a field research with qualitative methods and with historical and sociological analysis approaches. The results of this study conclude that traditional Islamic education in Minangkabau cannot be separated from the history of Islamization of Minangkabau itself, which is carried out through the Surau institution with the study of the Kitab Kuning (yellow book) and the teachings of its tarekats. However, at the beginning of the 20th century AD, the role of Surau was challenged by the modernization movement of Islamic education brought by young ulama. The existence of public schools established by the Dutch also further eliminates the educational position of the Surau.